UJI FITOKIMIA DAN AKTIVITAS ANTIBAKTERI EKSTRAK KASAR ETANOL, FRAKSI n-HEKSANA, ETIL ASETAT DAN METANOL DARI BUAH LABU AIR (Lagenari siceraria (Molina) Standl) - Eva Marliana; Chairul salaeh (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2011)
Phytochemical test and Antibacterial Activity test in each fraction of the gourds fruit (Lagenari siceraria (Molina) Standl) that came from Teluk Dalam, Tenggarong Seberang have been done. The sample of leaves was extracted with ethanol and then concentrated by using rotary evaporator. The ethanol crude extract was fractioned with n-hexane, Ethyl Acetate and Methanol. Based on the phytochemical test on secondary metabolits of the gourds fruit (Lagenari siceraria (Molina) Standl), it showed that ethanol crude extract contained flavonoid, saponin, steroid, and phenol. n-hexane fraction contained a steroid, ethyl acetate fraction contained phenol. And methanol-water fraction contained saponin and phenol. Based on the Antibacterial Activity test using the paper disc diffusion method (diameter 6 mm), the results of this test showed that the most active fraction is n-Heksana with : of the Bacillus cereus bacteria at the concentration 1, 2, 4, 6, 8 and 10% (b/v) with inhibition diameter 9.57, 9.88, 10.17, 12.18, 13 and 14.3 mm respectively so minimum inhibitory concentration got 0-1%. The active response toward Salmonella typhi bacteria at the concentration 1, 2, 4, 6, 8 and 10% (b/v) with inhibition diameter 7.50, 7.60, 8.20, 8.38, 8.87, and 9.8 mm so minimum inhibitory concentration got 0-1%. The chloramphenicol antibiotics concentration 0.00386 M as a standard to inhibit the growth of Bacillus cereus and Salmonella typhi bacteria with the inhibition diameter 12.58 mm and 15.06 mm respectively.